The Skill Structure of the Export Wage Premium: Evidence from German Manufacturing - Michael W Klein; Christoph Moser; Dieter M. Urban (Verein für Socialpolitik, 2010)
We find a significant export wage premium for higher-skilled workers and a significant export wage discount for lower-skilled workers, using a matched employer-employee data set for German manufacturing firms. Estimates suggest that up to one third of the overall skill premia is associated with exporting. These results imply that increasing trade contributes to widening wage inequality by skill level in manufacturing. But an increase in exports also diminishes wage discrimination due to gender or nationality. In this way, trade contributes to narrowing wage gaps and mitigates wage inequality in German manufacturing.
Keywords: F16; J31; J70; 330; exports; wages; wage inequality; wage discrimination; skill premia; linked employer-employee data